Exploring Abhakalan Culture (Early Marriage) in Madura: A Dialogue of Customary Law, Religion, and The State - Setiyawan, Deni; Wahyuningsih, Sri Endah; Hafidz, Jawade; Mashdurohatun, Anis; Benseghir, Mourad (Universitas Islam Negeri Jakarta, 2024)
This study explores the culture of Abhakalan in Madura in the context of early marriage, analyzing its intersections with customary law, religion, and the state. While aimed at preserving family honor, this practice often prioritizes the principle of ḍarran (harm), leading to gender inequality and injustices toward women. The research seeks to evaluate the implications of this cultural practice on women's rights and gender equality, using an empirical legal method grounded in conflict theory and social change, combined with Islamic concepts of ‘urf (accepted custom), naf'an (benefit), and ḍarran (harm). Findings indicate that Abhakalan culture denies women agency in marriage decisions, perpetuating stereotypes of female inferiority and limiting their opportunities for empowerment and education. This study highlights the need for cultural reform through gender advocacy, mindset shifts, and family economic empowerment. By fostering dialogue among customary law, religion, and state policies, the research underscores pathways to equitable and sustainable gender equality. AbstrakPenelitian ini mengkaji budaya Abhakalan di Madura dalam konteks pernikahan dini dengan menganalisis keterkaitannya dengan hukum adat, agama, dan negara. Meskipun bertujuan menjaga kehormatan keluarga, praktik ini sering mengedepankan prinsip ḍarran (bahaya) yang berujung pada ketidakadilan terhadap perempuan dan ketimpangan gender. Penelitian ini bertujuan untuk mengevaluasi dampak budaya ini terhadap hak-hak perempuan dan kesetaraan gender, menggunakan metode hukum empiris yang berlandaskan teori konflik dan perubahan sosial, serta konsep Islam seperti ‘urf (adat yang diterima), naf’an (manfaat), dan ḍarran (kerugian). Temuan menunjukkan bahwa budaya Abhakalan mengabaikan hak perempuan dalam pengambilan keputusan terkait pernikahan, memperkuat stereotip inferioritas perempuan, serta membatasi peluang pendidikan dan pemberdayaan mereka. Penelitian ini menekankan pentingnya reformasi budaya melalui advokasi gender, perubahan pola pikir, dan pemberdayaan ekonomi keluarga, dan dengan mendorong dialog antara hukum adat, agama, dan kebijakan negara, studi ini menawarkan langkah menuju kesetaraan gender yang adil dan berkelanjutan